Removal of the C-Terminal Domains of ADAMTS13 by Activated Coagulation Factor XI induces Platelet Adhesion on Endothelial Cells under Flow Conditions - Garland, Kathleen S.; Reitsma, Stéphanie E.; Shirai, Toshiaki; Zilberman-Rudenko, Jevgenia; Tucker, Erik I.; Gailani, David; Gruber, András; McCarty, Owen J. T.; Puy, Cristina (Frontiers in Medicine, 2017)
Platelet recruitment to sites of vascular injury is mediated by von Willebrand factor (VWF). The shear-induced unravelling of ultra-large VWF multimers causes the formation of a “stringlike” conformation, which rapidly recruits platelets from the bloodstream. A disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13) regulates this process by cleaving VWF to prevent aberrant platelet adhesion; it is unclear whether the activity of ADAMTS13 itself is regulated. The serine proteases α-thrombin and plasmin have been shown to cleave ADAMTS13. Based on sequence homology, we hypothesized that activated coagulation factor XI (FXIa) would likewise cleave ADAMTS13. Our results show that FXIa cleaves ADAMTS13 at the C-terminal domains, generating a truncated ADAMTS13 with a deletion of part of the thrombospondin type-1 domain and the CUB1-2 domains, while α-thrombin cleaves ADAMTS13 near the CUB1-2 domains and plasmin cleaves ADAMTS13 at the metalloprotease domain and at the C-terminal domain. Using a cell surface immunoassay, we observed that FXIa induced the deletion of the CUB1-2 domains from ADAMTS13 on the surface of endothelial cells. Removal of the C-terminal domain of ADAMTS13 by FXIa or α-thrombin caused an increase in ADAMTS13 activity as measured by a fluorogenic substrate (FRETS) and blocked the ability of ADAMTS13 to cleave VWF on the endothelial cell surface, resulting in persistence of VWF strands and causing an increase in platelet adhesion under flow conditions. We have demonstrated a novel mechanism for coagulation proteinases including FXIa in regulating ADAMTS13 activity and function. This may represent an additional hemostatic function by which FXIa promotes local platelet deposition at sites of vessel injury.